The Changes in Histopathology and Mass in Hyperbaric Oxygen–Treated Auricular Cartilage Grafts in a Rabbit Model - Bilici, Suat; Yiğit, Özgür; Dönmez, Zehra; Huq, Gülben Erdem; Aktaş, Şamil (Facial Plastic Surgery, 2015)
The aim of the study is to investigate the histopathologic and cartilage mass changes in hyperbaric oxygen (HBO)–treated auricular cartilage grafts either crushed or fascia wrapped in a rabbit model. This is a prospective, controlled experimental study. Sixteen rabbits were randomly allocated into control (n = 8) and treatment groups (n = 8). Each group was further grouped as crushed cartilage (n = 4) and fascia wrapped crushed cartilage (n = 4). The eight rabbits in the treatment group had HBO once daily for 10 days as total of 10 sessions. The mass of cartilage, cartilage edge layout, structural layout, staining disorders of the chondroid matrix, necrosis, calcification besides bone metaplasia, chronic inflammation in the surrounding tissues, fibrosis, and increased vascularity were evaluated in the hematoxylin and eosin (H&E)–stained sections. Fibrosis in the surrounding tissue and cartilage matrix was evaluated with Masson's trichrome stain. The toluidine blue staining was used to evaluate loss of metachromasia in matrix. The prevalence of glial fibrillary acidic protein (GFAP) staining in chondrocytes was also evaluated. Although the remaining amount of cartilage mass after implantation does not show a significant difference between the control and the study group (p = 0.322, p <0.05).The difference between control and study group in terms of positive staining with GFAP was statistically significant (p = 0.01, p <0.05). Necrosis and loss of matrix metachromasia were significantly low in the study group compared with control group (p = 0.001, p = 0.006, p <0.05). HBO therapy did not have significant effect on the mass of rabbit auricular cartilage graft. HBO therapy significantly reduced loss of metachromasia, necrosis, and GFAP staining in the auricular cartilage grafts of the animal model.
Keywords: hyperbaric oxygen therapy; crushed cartilage; cartilage mass